The Middle Pleistocene to early Holocene subsurface geology of the Norderney tidal basin: new insights from core data and high-resolution sub-bottom profiling (Central Wadden Sea, southern North Sea). (14th May 2021) - Schaumann, Robin M.; Capperucci, Ruggero M.; Bungenstock, Friederike; McCann, Tom; Enters, Dirk; Wehrmann, Achim; Bartholomä, Alexander
Abstract: Pleistocene strata of the Wadden Sea region are mostly covered by an up to 10m thick sediment wedge deposited during the Holocene transgression. However, tidal inlets cut deep into the Holocene succession, causing Middle Pleistocene to early Holocene glacial and interglacial deposits to outcrop at the channel bottom. To investigate how the lithological properties and/or morphologies of these deposits affect the development of Holocene tidal inlets (e.g. limiting erosional processes), we analysed a series of eight cores to verify three high-resolution sub-bottom transects – and thus – to extend point-based data over a broader area. Furthermore, eight additional new cores (16 WASA cores in total), and 14 reinterpreted cores from the LBEG (Geological Survey of Lower Saxony) log database, were correlated to generate three short cross-sections at the transition from the tidal inlet (Riffgat channel) to the island of Norderney, revealing a number of new aspects for the reconstruction of the Pleistocene palaeoenvironments, i.e. the last two glacials (Saalian and Weichselian) and interglacials (Holsteinian? and Eemian). A succession of Middle Pleistocene lacustrine delta deposits, belonging either to the Holsteinian or the Dömnitz temperate stage, suggests the presence of Elsterian tunnel valleys located below the island. Furthermore, we verified the presence of an Eemian mixed tidal-flat system overlain by an Eemian sand tidal flat below the western head of Norderney which is, in contrast to suggestions from previous studies, not fully eroded in this area. Finally, we demonstrate that the Saalian moraine (Drenthe Main Till) functions as a limiting constraint in the vertical development of the Holocene/modern Riffgat channel. Our results provide a better understanding of the Quaternary stratigraphy of the central Wadden Sea as well as the influence of the subsurface geology on the architecture and evolution of tidal channels.